The effect of time of measurement on the discriminant ability for mortality in trauma of a pre-hospital shock index multiplied by age and divided by the Glasgow Coma Score: a registry study - Mikael Laaksonen; Johannes Björkman; Timo Iirola; Lasse Raatiniemi; Jouni Nurmi (BMC Emergency Medicine, 2022)
Abstract Background The shock index (SI) and its derivatives have been shown to predict mortality in severely injured patients, both in pre-hospital and in-hospital settings. However, the impact of the time of measurement on the discriminative ability of the pre-hospital SI is unknown. The aim of this study was to evaluate whether the time of measurement influences the discriminative ability of the SI multiplied by age (SIA) and divided by the Glasgow Coma Score (SIA/G). Methods Registry data were obtained from the national helicopter emergency medical services (HEMS) on trauma patients aged ≥ 18 years. The SI values were calculated based on the first measured vitals of the trauma patients by the HEMS unit. The discriminative ability of the SIA/G, with 30-day mortality as the endpoint, was evaluated according to different delay times (0 − 19, 20 − 39 and ≥ 40 min) from the initial incident. Sub-group analyses were performed for trauma patients without a traumatic brain injury (TBI), patients with an isolated TBI and patients with polytrauma, including a TBI. Results In total, 3,497 patients were included in the study. The SIA/G was higher in non-survivors (median 7.8 [interquartile range 4.7–12.3] vs. 2.4 [1.7–3.6], P < 0.001). The overall area under the receiver operator characteristic curve (AUROC) for the SIA/G was 0.87 (95% CI: 0.85–0.89). The AUROC for the SIA/G was similar in the short (0.88, 95% CI: 0.85–0.91), intermediate (0.86, 95% CI: 0.84–0.89) and long (0.86, 95% CI: 0.82–0.89) measurement delay groups. The findings were similar in the three trauma sub-groups. Conclusions The discriminative ability of the SIA/G in predicting 30-day mortality was not significantly affected by the measurement time of the index in the pre-hospital setting. The SIA/G is a simple and reliable tool for assessing the risk of mortality among severely injured patients in the pre-hospital setting.